Mayo Clinic antimicrobial therapy : quick guide - Wilson, John W., 1967-; Estes, Lynn L.; Mayo Clinic ([New York] : Oxford University Press, 2018)
This work provides information about infectious diseases and antimicrobial therapy in a format that is readily accessible and easily applicable to the clinical environment.
This edition previously issued in print: 2018.
Includes bibliographical references.
Specialized.
Description based on online resource; title from home page (viewed on August 22, 2018).
Keywords: Anti-infective agents -- Handbooks, manuals, etc; Communicable diseases -- Chemotherapy -- Handbooks, manuals, etc